2023
DOI: 10.3390/polym15030740
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Fatigue Properties of Rejuvenated Asphalt Prepared by Waste Cooking Oil Pre-Desulfurized Crumb Tire Rubber

Abstract: Fatigue cracking has hitherto been a crucial constraint on the development of reclaimed asphalt pavements attributed to the performance of rejuvenated asphalt binder. Therefore, it is extremely significant to evaluate the fatigue performance of rejuvenated asphalt precisely and objectively and to improve the fatigue life of rejuvenated asphalt binders. With preceding research in our group, this paper investigated the fatigue properties of waste rubber/oil (WRO) rejuvenated asphalt and universal rejuvenated asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In the realm of pavement engineering, recent studies have explored innovative approaches to incorporate recycled materials and by-products [ 13 , 14 ], with a specific focus on enhancing the sustainability and performance of asphalt mixtures. Dong et al investigated the utilization of recycled rubber and reported improvements in asphalt mixtures’ flexibility and fatigue resistance [ 15 ]. Li et al delved into the application of reclaimed asphalt pavement (RAP) and observed enhanced pavement durability and reduced environmental impact [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of pavement engineering, recent studies have explored innovative approaches to incorporate recycled materials and by-products [ 13 , 14 ], with a specific focus on enhancing the sustainability and performance of asphalt mixtures. Dong et al investigated the utilization of recycled rubber and reported improvements in asphalt mixtures’ flexibility and fatigue resistance [ 15 ]. Li et al delved into the application of reclaimed asphalt pavement (RAP) and observed enhanced pavement durability and reduced environmental impact [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pavement quality in tropical climates can be compromised by various factors, including acid rain, traffic oils, and municipal debris, which can lead to pavement deterioration [34]. Therefore, this research aims to investigate the feasibility of using a polymer-modified asphalt concrete mixture to improve the durability of pavement under tropical climate conditions.…”
Section: Introductionmentioning
confidence: 99%